Penerimaan Teknologi Gawai dalam Menonton Pertunjukan Teater Virtual di Era Pandemi Covid 19 - Gamaliel Paulus (Communication Science Department - Faculty of Social and Political Sciences, Universitas Satya Negara Indonesia (USNI), 2022)
The COVID-19 pandemic that has hit Indonesia since March 2020, has had a bad impact not only on the economy and health fields, but also in various fields of life. One of those is theater performing arts. The social restrictions imposed by the government have resulted in many theater groups being unable to conduct theatrical performances. People should stay at home more and use various communication technologies to interact with each other. In order to keep the theater performing arts alive, theater workers took the initiative to organize virtual theater where audience can watch theater through their various devices. The experience of watching a virtual theater is certainly different from the experience of watching live in a theater building. This study wants to see the experience of theater fans when they have to watch the theater virtually. This research uses a descriptive qualitative approach with case study method focusing on d'Art Beat theater audiences through interviews and observations. The theory used in the interview with theater audiences is Technology Acceptance Model which looks at the audience's acceptance and experience in using gadget technology as a medium for watching theater compared to watching it live in a theater building. The temporary findings shows that the experience of watching theatrical art performances virtually cannot replace the satisfaction of watching it live. This is because basically theatrical art is a a stage drama performance which involves players on stage and audience watching directly in a theater building.